Impact of Artificial Intelligence on Employment Generation - Poornima B. S., (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2025)
India has emerged as a global economic powerhouse, boasting the world’s fifth-largest economy. With a GDP projected to reach $15 trillion by 2030, India aims to become the third-largest economy globally. This remarkable growth trajectory is driven by a mixed economy model, where the public and private sectors coexist. Historically, agriculture has been the backbone of the Indian economy, supporting a significant portion of the population. However, the focus has gradually shifted towards technological advancements, as evident in initiatives like Digital India and the adoption of Artificial Intelligence (AI). These advancements aim to modernize various sectors, improve efficiency, and enhance overall economic competitiveness. Despite impressive growth, India faces several challenges, including poverty, income inequality, unemployment, and environmental concerns. Unemployment, in particular, remains a significant hurdle. While AI offers immense potential for economic growth and innovation, its impact on employment in developing countries like India remains a complex issue. AI can automate tasks, improve decision-making, and create new job opportunities. However, it also poses risks such as job displacement, the need for reskilling, and the exacerbation of existing inequalities. The fear is that AI may disproportionately impact low-skilled workers in developing countries, leading to further job losses and social unrest. Therefore, India needs to carefully navigate the AI revolution. While embracing AI’s potential for economic growth, it is crucial to mitigate the potential negative impacts on employment. This requires proactive measures such as:: Equipping the workforce with the necessary skills to adapt to an AI-driven economy, Providing support to those who may lose their jobs due to automationandensuring that AI technologies are developed and deployed responsibly, considering their social and ethical implications.By strategically leveraging AI while addressing its potential downsides, India can harness the power of technology to drive inclusive and sustainable economic growth, ensuring that the benefits of progress are shared by all its citizens.This article looks at the employment situation in India, AI impact on employment and explains AI and Employment in global level and India. This paper based on secondary sources. The findings of this study contribute to the understanding of the AI impact of modern digital technologies on the employment generation in India as well as people in developing countries. Indian Employment growth rate is very low and Unemployment rates are declining recent years. AI benefit for developed countries, not for developing countries. Developing countries already having unemployment problems and high population density. So AI negatively impact in developing countries like India. Because the Indian economy has not able to create enough remunerative jobs in the non-farm sectors for new educated youth labour force jobseekers, which is reflected in the high and increasing unemployment rate.” In Indian context AI benefit take long term on employment generation.
Keywords: Indian Economy; Employment; Artificial Intelligence; Unemployment